2005
DOI: 10.1007/s00038-005-3148-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between unfavourable health status and smoking cessation attempts in Hungary

Abstract: Connections between health status and quitting intentions are weakening as age is increasing. The population seems to become gradually conscious of the connections between circulatory problems and smoking. Quitting attempts are restrained by the general attitude that ill health is a normal part of the ageing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…this finding is consistent with the study 24 which reported that experiences of chest pain, suffering from cardio vascular disease and respiratory diseases had influenced quitting attempts. A study 25 showed that when nurses offered smoking cessation advice and intervention, patients were more likely to quit than when nurses offered no intervention at all.…”
Section: Resultssupporting
confidence: 93%
“…this finding is consistent with the study 24 which reported that experiences of chest pain, suffering from cardio vascular disease and respiratory diseases had influenced quitting attempts. A study 25 showed that when nurses offered smoking cessation advice and intervention, patients were more likely to quit than when nurses offered no intervention at all.…”
Section: Resultssupporting
confidence: 93%
“…Most studies that address determinants of quit attempts are based on specific populations such as adolescents or young adults [8-10], hospital/clinic and/or chronically-ill patients [9,11-14], specific race/ethnic background, or non-US populations [15-19]. Few studies have assessed quit attempts in the general population [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In discussing the social norms about smoking in Hungary it is important to detail the smoking situation in that country, which suggests a tolerance for smoking. Approximately 25 billion cigarettes are smoked in Hungary per year and one‐third of the Hungarian population ≥15 years of age are regular daily smokers 25 . Despite public health and regulatory efforts to decrease smoking in the country, and associated high smoking‐attributable deaths, the proportion of smokers aged 15–18 years increased from 37.3% to 45.3% between 1995 and 2000.…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that the estimations of the Hungarian students versus the US students were also substantially higher for the percentage of eighth grade students (63% vs 30%), college students (79% vs 53%), and adults (79% vs 56%) perceived to be smokers. Only limited research to date has examined factors shaping adolescents' perceptions of the prevalence of smoking, and that research suggested that close friends' smoking; seeing smoking at school; family members' smoking; parental smoking; and smoking status were possible determinants of these perceptions 25 . It is plausible that there are important differences in the factors shaping these perceptions among Hungarian adolescents than among other populations of adolescents.…”
Section: Discussionmentioning
confidence: 99%